The role of sample height in the stacking diagram of colloidal mixtures under gravity. (21st December 2016) - Geigenfeind, Thomas; de las Heras, Daniel
Abstract: Bulk phase separation is responsible for the occurrence of stacks of different layers in sedimentation of colloidal mixtures. A recently proposed theory (de las Heras and Schmidt 2013 Soft Matter 9 8636) establishes a unique connection between the bulk phase behaviour and sedimentation-diffusion-equilibrium. The theory constructs a stacking diagram of all possible sequences of stacks under gravity in the limit of very high (infinite) sample heights. Here, we study the stacking diagrams of colloidal mixtures at finite sample height, h . We demonstrate that h plays a vital role in sedimentation-diffusion-equilibrium of colloidal mixtures. The region of the stacking diagram occupied by a given sequence of stacks depends on h . Hence, two samples with different heights but identical colloidal concentrations can develop different stacking sequences. In addition, the stacking diagrams for different heights can be qualitatively different since some stacking sequences occur only in a given interval of sample heights. We use the theory to investigate the stacking diagrams of both model bulk systems and mixtures of patchy particles that differ either by the number or by the types of patches.